Klasifikasi Penyakit Daun Tomat Menggunakan MobileNetV3 - Russel Wijaya; Nur Rachmat (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Tomato (Solanum lycopersicum) is a high-value horticultural commodity in Indonesia, yet its cultivation is frequently disrupted by leaf diseases that are difficult to distinguish visually. Diseases such as Bacterial Spot, Early Blight, and Tomato Yellow Leaf Curl Virus often present overlapping visual symptoms, making early and accurate diagnosis a significant challenge for farmers. The manual identification methods currently in use are inefficient and error-prone, ultimately leading to reduced crop yield and quality. The general objective of this study is to develop software capable of automatically classifying tomato leaf diseases. Specifically, this research aims to implement the MobileNetV3 Small architecture based on Convolutional Neural Network (CNN) with ImageNet pre-trained weights to classify 10 types of tomato leaf diseases. The research methodology encompasses dataset collection from Kaggle comprising 10,000 images (1,000 per class), image pre-processing through resizing to 224x224 pixels, and normalization, as well as hyperparameter optimization (optimizer, learning rate, epoch, batch size) via scheduler. Model performance is evaluated using a confusion matrix encompassing accuracy, precision, recall, and F1-score.